Implementation of household-scale clean water treatment technology for the mountain farming community, Jajar village, Gandusari district, Trenggalek - Wahyu Dwi Lestari; Luluk Edahwati; Wiliandi Saputro (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
Currently, the need for clean water which is a vital source for people's lives has not been fully met for all Indonesians, including the mountain farming community, Jajar Village, Gandusari District, Trenggalek Regency. So far, the mountain farming community members of Jajar Village have used mountain water for household needs where cloudy and unstable water conditions are a problem that must be faced. If this problem continues, it will lead to serious health problems and social conflicts in the community. Therefore, through community service activities, we made a practical clean water treatment tool, with easily obtained materials, that can be implemented in hilly areas such as in Jajar Village, Gandusari District, Trenggalek Regency. The filtration system used is an upflow and downflow system where the water undergoes a filtration process twice in the material that has been selected and arranged in a systematic way. The materials used are available and easy to obtain in Jajar Village, so that people can discover easily about the benefits of these materials. After making a water filtration system with the community, then physical testing is conducted on the quality of the water produced. From the test results of the effectiveness of the implementation of clean water treatment technology applied to mountain farmers in Jajar Village, it shows that in general the filtered water has met the physical requirements for the level of turbidity, taste, and smell, as well as the quantity and continuity of water are always available when needed.